Investigations on Spray Characteristics and Self-Pulsation of a Gas-Centered Shear Coaxial Injector - Yuchao, Gao; Wei, Chu; Yuan, Xie; Chuanjin, Jiang; Boqi, Xu; Lingyu, Su; Yiheng, Tong (Frontiers in Energy Research, 2022)
The spray characteristics of a gas-centered shear coaxial injector under different conditions and recess ratios (RR) were studied through experiments and numerical simulations. The numerical study was carried out based on the coupled level set and volume-of-fluid (CLSVOF) method and the adaptive mesh refinement (AMR) method. The results indicated that without recess, the spray angle first stayed almost constant and then dropped linearly with an increase in the gas mass flow rate (m˙g) when holding the liquid mass flow rate (m˙l) constant. In contrast, with recess, the spray angle was found to increase with m˙g, which could be attributed to the secondary expansion of the central gas flow. Under specific conditions, self-pulsation occurred and was accompanied by a loud scream. The frequency of the self-pulsation increased with both m˙g and m˙l. Moreover, the self-pulsation frequency decreased with RR. Meanwhile, the mechanism of self-pulsation was initially explored through numerical simulation. It was concluded that self-pulsation was caused by the surface tension and the pressure difference between the inside and outside of the liquid sheet, together with the central airflow impact extrusion.